Zuccagnia‐type Propolis from Argentina: A potential functional ingredient in food to pathologies associated to metabolic syndrome and oxidative stress - Salas, Ana Lilia; Mercado, María Inés; Orqueda, Maria Eugenia; Correa Uriburu, Florencia; García, Maria Elena; Pérez, María Jorgelina; Alvarez, María de los Angeles; Ponessa, Graciela I.; Maldonado, Luis Maria; Zampini, Iris Catiana; Isla, María Inés (Wiley, 2020)
The effect of Argentine propolis extracts against enzymes related to metabolic syndrome and oxidative stress, as well as the botanical origin of raw propolis, were studied. Histological and chemical analyses of propolis samples revealed that the botanical origin is Zuccagnia punctata , an Argentine medicinal plant. The melissopalynological analysis showed both pollen grains of Z. punctata and the other plant species. This result indicates that the differences found in the botanical remains compared to the palynological studies may have been caused by the bees selecting resinous shrubs mainly of Z. punctata for the production of propolis and other plants with flowers for the production of honey. The richness of propolis was remarkable in two flavonoid precursors (2´,4´‐dihydroxy‐3´‐methoxychalcone, 2´,4´‐dihydroxychalcone), the major chemical components of Z. punctata . The hydroalcoholic extracts of Argentine propolis and Z. punctata were able to inhibit enzymes associated with the metabolic syndrome, including α‐glucosidase, α‐amylase and lipase, with IC50 values between 7 to 14, 37 to 48, and 13 to 28 µg/mL, respectively. Biological activity was mainly attributed to chalcones. Oxygen and nitrogen reactive species scavenging activity was determined by the assays of superoxide radical (O2•−), hydroxyl radical (HO•), hydrogen peroxide (H2O2), nitric oxide (NO•), and cation radical (ABTS•+). Results showed SC50 values between 115 to 278, 12.50 to 46; 39 to 92; 50 to 104.50 and 23 to 33.75 µg/mL, respectively. This study suggests for the first time that propolis from Argentina is highly effective in inhibiting enzymes related to the metabolic syndrome and in free‐radical scavenging that would justify its use as a dietary supplement or as a functional ingredient in special food. Practical Application: Propolis from Catamarca, Argentina, is traditionally used as medicine and food. Its botanical origin is Zuccagnia punctata , an endemic plant species popularly used as a medicine in Argentina. Propolis has the ability to regulate the activity of enzymes involved in the carbohydrate and lipid metabolism, and consequently in metabolic syndrome. Besides, its antioxidant capacity makes it a natural product that can be used as a dietary supplement or as a functional ingredient in special foods. It is important to highlight that in the Argentine Food Code, propolis was incorporated in 2008 as a dietary supplement and the present results give major added value to this product.